Phenotypic characteristics and risk factors in a multi-ethnic cohort of young adults with type 2 diabetes. (2nd November 2019) - Lascar, Nadia; Altaf, Quratul-Ain; Raymond, Neil T.; E. P. Brown, James; Pattison, Helen; Barnett, Anthony; Bailey, Clifford J.; Bellary, Srikanth
Abstract: Background: Early onset of type 2 diabetes (T2DM) is associated with prolonged exposure to hyperglycaemia and increased propensity to chronic complications. The aim of this study was to characterize and compare the phenotypic characteristics and risk factors in a multi-ethnic cohort of young adults with type 2 diabetes (T2DMY). Methods: One hundred young adults (White European [WE], South Asian [SA] and African-Caribbean [AC]) diagnosed with T2DM before the age of 40 years were recruited. Demographics, family history, diabetes related complications, co-morbidities, anthropometry (body mass index [BMI], body composition), physical activity and biochemistry (HbA1c, lipid profile, liver and renal function) and autoantibodies (anti GAD, anti islet cell) were collected for all participants. Data were analysed for the most represented ethnic groups: (WE, N =  36 and SA, N =  53) using SPSS version 23. Results: Mean (± standard deviation) age at diagnosis was 32.5 ± 5.5 years and mean diabetes duration was 7.7 ± 3.8 years. Overweight/obesity was present in 95% of participants, history of maternal diabetes in 68%, deprivation 75%, low physical activity 40%, polycystic ovarian disease 29% (in females), acanthosis nigricans 12% and non-alcoholic fatty liver 11%. There was considerable clustering of risk factors within the cohort with over 75% of all subjects having three or more of the above risk factors and 52% required insulin within 3 years of diagnosis. Two-thirds of the patients had evidence of at least one diabetes related microvascular complication. Conclusion: T2DMY is characterized by a high burden of commonly associated risk factors for both the disease and its long-term complications.